THE DATA MINING OF CELL PHONE MOST INTERESTED USING APRIORIAL ALGORITHM - Penda Sudarto Hasugian; Suprianto Panjaitan (Sean Institute, 2023)
Data mining is a term used to describe knowledge discovery in a database or often called Knowledge Discovery in Database (KDD). With the development of information at this time, the need for accurate information is needed in daily life, so that information will become an important element in the development of society today and the future. However, high information needs are sometimes not balanced by the presentation of adequate information, often the information must still be extracted from very large amounts of data. The ability of information technology to collect and store various types of data far leaves the ability to analyze, summarize and extract knowledge from data. Decision-makers try to utilize data warehouse that has been owned to dig up information that is useful to help make decisions, this encourages the emergence of new branches of science to overcome the problem of extracting information or patterns that are important or interesting from large amounts of data, which is called data mining. The use of data mining techniques is expected to provide knowledge previously hidden in the data warehouse so that it becomes valuable and useful information.